Advancing Green Work Engagement In Healthcare: A Systematic Review And Future Research Directions - Fajar Satria; Ahmad Hidayat Sutawijaya; Abdul Haeba Ramli; Triyono Arief Wahyudi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The healthcare sector, while central to public well-being, is paradoxically responsible for 4–5% of global greenhouse gas emissions. This systematic literature review (SLR) critically explores the emerging concept of Green Work Engagement (GWE)—defined as employees’ proactive involvement in sustainable practices—and its transformative potential for healthcare institutions. Guided by the PRISMA framework, this review synthesizes high-quality studies from 2014 to 2024, identifying leadership, organizational support, environmental awareness, and green HRM as pivotal antecedents of GWE. Findings highlight that green servant leadership and green talent management foster innovative behaviors, enhance job satisfaction, and improve both environmental performance and clinical outcomes. Technological integration (e.g., cloud computing) and structured frameworks (e.g., GreenEd, 5R) also emerge as key enablers of systemic change. However, the literature reveals methodological gaps, limited application in developing contexts, and insufficient empirical evaluation of behavioral interventions. This study offers a robust conceptual foundation and practical roadmap for embedding sustainability into healthcare operations, emphasizing the role of leadership, employee engagement, and inclusive organizational culture in advancing environmental stewardship. The review concludes with actionable research directions to strengthen the theoretical and practical relevance of GWE and support the healthcare sector’s alignment with global sustainability goals. Keywords: Green Work Engagement, Healthcare Sustainability, Green HRM, Employee Engagement, Environmental Leadership, Systematic Review